Peran Tabungan IB Simpel Dalam Perkembangan PT Bank Sumut KCP Syariah Simpang Kayu Besar - Ruqayyah Ruqayyah; Nurul Jannah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This research is motivated by the role of savings services provided by the Islamic Bank of North Sumatra, namely the Simple IB Savings which makes it easier for students to save money and open savings. This research is expected to provide results or conclusions that can be useful for all parties. The purpose of writing this paper is to provide an overview to the Management of Bank Sumut that it is important to gather all students in North Sumatra by joining PT Bank Sumut by using the Simple Program. The formulation of the problem in this study is (1) What is the role of simple IB savings in the development of the Simpang Kayu Besar Syariah Bank? (2) Does the Simple Savings market marketed by PT Bank Sumut to students grow third party funds and the image of Bank Sumut?. This study uses a qualitative approach with descriptive qualitative methods which in its implementation this study uses data collection techniques in the form of interviews, questions and answers, observations and the results of the research can be in the form of words or statements that are appropriate to use the actual situation. Primary data is obtained directly from the results of the interview of the parties concerned as well as documentation or company archives. Secondary data is obtained from the literature related to the material to be discussed, either in the form of journal source books, newspapers or from sources relevant to the subject matter in the preparation of this journal. The results of this study indicate the number of prospective customers who can be used in finding customers every year the number of students will continue to grow, with a good relationship and good communication, of course these prospective customers will continue to grow not only among students.